2014
DOI: 10.1007/s00253-014-5882-5
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Escherichia coli for odd straight medium chain free fatty acid production

Abstract: Microbial biosynthesis of free fatty acids (FFAs) can be achieved by introducing an acyl-acyl carrier protein thioesterase gene into Escherichia coli. The engineered E. coli usually produced even chain FFAs. In this study, propionyl-CoA synthetase (prpE) from Salmonella enterica was overexpressed in two efficient even chain FFAs producers, ML103 (pXZM12) carrying the acyl-ACP thioesterase gene from Umbellularia californica and ML103 (pXZ18) carrying the acyl-ACP thioesterase gene from Ricinus communis combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…It is reported that exogenous propionate (C3) can be used as a primer for synthesis of odd chain fatty acids: Propionate can be converted to propionyl-CoA by propionyl-CoA synthase, and propionyl-CoA is condensed with malonyl-CoA in the first step of odd chain fatty acid synthesis [ 15 ]. A metabolic engineering strategy with propionate supplementation achieved a production of 0.276 g/L odd chain free fatty acids in E. coli [ 16 ]. In addition, further engineering of E. coli showed an increased percentage of odd chain free fatty acids in total free fatty acids by 6.25-fold with propionate supplementation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that exogenous propionate (C3) can be used as a primer for synthesis of odd chain fatty acids: Propionate can be converted to propionyl-CoA by propionyl-CoA synthase, and propionyl-CoA is condensed with malonyl-CoA in the first step of odd chain fatty acid synthesis [ 15 ]. A metabolic engineering strategy with propionate supplementation achieved a production of 0.276 g/L odd chain free fatty acids in E. coli [ 16 ]. In addition, further engineering of E. coli showed an increased percentage of odd chain free fatty acids in total free fatty acids by 6.25-fold with propionate supplementation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…By supplying endogenous propionyl-CoA from oxaloacetate through a newly introduced synthetic pathway, the engineered strain with the genetic background for high lipid production was able to produce OCFAs without the supplementation of propionic acid (Park et al, 2020; Figure 4B). In E. coli, the overexpression of propionyl-CoA synthase from Salmonella enterica and acyl-ACP thioesterase from Ricinus communis and Umberllularia california enabled the production of 276 mg/L of OCFAs, with chain lengths of C11-C15, comparable to that in Y. lipolytica, in the presence of optimized propionate supplementation (Wu and San, 2014).…”
Section: Odd-chain Fatty Acids (Ocfas)mentioning
confidence: 99%
“…development of yeast cell factories. Interestingly, unconventional carbon sources other than glucose, such as xylose, acetate, and propionic acid, have been shown to better support metabolic flux through the biosynthesis pathway for non-native chemicals (Wu and San, 2014;Li et al, 2017;Portugal-Nunes et al, 2017;Wu et al, 2019). Thus, non-native chemical production by the engineered yeast strains with non-native carbon metabolism could offer better promises for industrial-scale production of non-native chemicals.…”
Section: Challenges and Opportunities In Non-native Chemical Productionmentioning
confidence: 99%
“…However, most microorganisms require the presence of propionate in the medium to produce odd-chain FAs. Wu and San have shown that E. coli can produce odd-chain FAs-namely undecanoic acid (C11:0), tridecanoic acid (C13:0), and pentadecanoic acid (C15:0)-if grown with propionatesupplemented medium (Wu and San, 2014). They introduced a propionyl-CoA synthetase (prpE) from Salmonella enterica and acyl-ACP thioesterases (TEs) from Umbellularia californica and FIGURE 1 | Lipid synthesis in Y. lipolytica.…”
Section: Introductionmentioning
confidence: 99%